Physician specialization and women's primary care services in an urban HIV clinic. - Koethe, John R; Moore, Richard D; Wagner, Krystn R (AIDS patient care and STDs, 2008)
To compare adherence to published primary care guidelines by general internal medicine and infectious diseases (ID) specialist physicians treating HIV-positive women we conducted a retrospective patient record review of 148 female HIV-positive patients seen at the Nathan Smith Clinic in New Haven, Connecticut, in 2001 and 2002. Four quality measures were defined to evaluate physician practices: annual cervical cancer screening, influenza vaccination and hyperlipidemia screening, and biennial mammography. Main outcome was the frequency of meeting each measure by generalist and ID-specialist physicians, and the two physician types were compared after controlling for patient clustering, age, and CD4 cell count. Among all measures, the rates of cervical cancer screening in 2001 were lowest among generalists (55%) and ID-specialists (47%) but not significantly different (odds ratio [OR] 1.26, 95% confidence interval [CI] 0.78 to 1.90), and the rates of hyperlipidemia screening in 2002 were highest for both generalists (98%) and ID-specialists (93%), but again not significant (OR 2.86, CI 0.30 to 27.6). No statistically significant differences were found between physician types for any quality measure, nor were significant differences found in the CD4 cell counts of patients of each physician type who received each service. Our results show potential for improvements in care among both generalist and ID-specialist physicians treating HIV-positive women.
Keywords: Communicable Diseases; Connecticut; Female; Guideline Adherence; HIV Infections; Humans; Hyperlipidemias; Influenza Vaccines; Internal Medicine; Mammography; Medicine; Physician's Practice Patterns; Primary Health Care; Specialization; Urban Health; Vaginal Smears